Effect of Chemical Precursors On the Optical and Electrical Properties of p‐Type Transparent Conducting Cr2O3:(Mg,N) - FLEISCHER, KARSTEN; ARCA, ELISABETTA; SHVETS, IGOR (My University, 2013)
Cr2O3:(Mg,N) has been reported as a p-type transparent conducting oxide. In this contribution the effect of each precursor used for the deposition by spray-pyrolysis, will be explored and their role in determining the optical and electrical properties of Cr2O3 will be outlined. A correlation between the structural, electrical, and optical properties upon introducing nitrogen precursors has been established. In particular it has been shown that the presence of ammonium salts in the deposition environment results in less absorbing films. By combining optical measurements and NEXAFS studies, a mechanism is proposed to explain the change in the optical properties. Moreover, it is shown that the presence of the nitrate moiety in the reaction environment is necessary to improve the electrical conductivity of the deposited films. The reaction of the nitrate moiety with the ammonium moiety has been proposed as the mechanism to explain the boost in conductivity.
PUBLISHED
Keywords: defect chemistry; p-type TCO; Cr2O3; nexafs; spray pyrolysis; transparent conducting oxide; Nanoscience & Materials; Smart & Sustainable Planet